3
$\begingroup$

Prove that

$$\neg (\neg P \lor (P \land \neg Q)) \equiv P \land Q$$

without using truth tables. Instead, use various logic properties like De Morgan's, etc.

$\endgroup$
3
$\begingroup$

Using de Morgan's laws:

$$\neg(\neg P\lor (P\land \neg Q))\equiv \neg\neg P\land \neg(P\land \neg Q)$$

$$\equiv P\land (\neg P\lor \neg\neg Q)$$

$$\equiv P\land (\neg P\lor Q)$$

$$\equiv (P\land \neg P)\lor(P\land Q)$$

$$\equiv P\land Q.$$

$\endgroup$
1
$\begingroup$

$$\neg(\neg P \lor (P\land\neg Q)) \leftrightarrow P\land Q$$ $$ P \land \neg(P\land\neg Q)\leftrightarrow P\land Q$$ $$ P \land (\neg P\lor Q)\leftrightarrow P\land Q$$ $$ (P \land \neg P )\lor( P\land Q)\leftrightarrow P\land Q$$ $$ P\land Q\leftrightarrow P\land Q$$

$\endgroup$
1
$\begingroup$

Hint : a repeated application of DeMorgan's is all you need.

To start, $$\neg (\neg P \lor (P \land \neg Q)) = P \land (\neg{(P \land \neg Q))} $$

Can you proceed?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.